Příprava a realizace mezinárodního závodu ve freestyle lyžování - Chrástecký, Martin (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Bakalářská práce je zaměřena na přípravu a realizaci mezinárodního závodu v lyžování. Práce je členěna do několika části. Teoretická část se zabývá tvorbou podnikatelského plánu, SWOT analýzou, PEST analýzou, marketingovým mixem, dotazníkem, rozpočty a kalkulacemi a analýzou konkurenčního prostředí. Tyto poznatky jsou aplikovány v praktické části, v které je také navrhnuta inovace závodu.

Bachelor thesis is focused on the preparation and implementation of an international competition in skiing. Work is divided into several parts. The theoretical part deals with the creation of a business plan, SWOT analysis, PEST analysis , marketing mix, questionnaire, budgets and calculations and analysis of the competitive environment . These findings are applied in the practical part, which is also designed to upgrade the plant.
Preparation and Implementation of an International Race in Freestyle Skiing
Keywords: Podnikatelský záměr; sportovní akce; SWOT analýza; freeskiing; marketingový mix; kalkulace; rozpočet; sport; lyžování; PEST analýza; dotazník; Business plan; sporting events; SWOT analysis; freeskiing; marketing mix; calculation; costing; sport; skiing; PEST analysis; questionnaire